Intel Galileo blueprints : discover the true potential of the Intel Galileo board for building exciting projects in various domains such as home automation and robotics /: discover the true potential of the Intel Galileo board for building exciting projects in various domains such as home automation and robotics. (2015) - Schwartz, Marco
No abstract available